2023
DOI: 10.1039/d3fo01608k
|View full text |Cite
|
Sign up to set email alerts
|

Tomato-fruit-derived extracellular vesicles inhibit Fusobacterium nucleatum via lipid-mediated mechanism

Bao-Hong Lee,
She-Ching Wu,
Hao-Yuan Chien
et al.

Abstract: Extracellular vesicles derived from tomato have potential on regulating gut microbiota.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 43 publications
(61 reference statements)
0
14
0
Order By: Relevance
“…In addition, this was verified not only in ginger-derived nanovesicles, but also in tomato-derived nanovesicles. Gorevic et al found that tomato-derived nanovesicles were also taken up by Fusobacterium nucleatum and that this uptake process was also dependent on lipid components [ 14 ]. When lipids were removed, the uptake of tomato-derived nanovesicles by Fusobacterium nucleatum was reduced and their growth state was restored [ 14 ].…”
Section: Endocytosis: Specific Recognition and Uptake By Microbial Co...mentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, this was verified not only in ginger-derived nanovesicles, but also in tomato-derived nanovesicles. Gorevic et al found that tomato-derived nanovesicles were also taken up by Fusobacterium nucleatum and that this uptake process was also dependent on lipid components [ 14 ]. When lipids were removed, the uptake of tomato-derived nanovesicles by Fusobacterium nucleatum was reduced and their growth state was restored [ 14 ].…”
Section: Endocytosis: Specific Recognition and Uptake By Microbial Co...mentioning
confidence: 99%
“…Gorevic et al found that tomato-derived nanovesicles were also taken up by Fusobacterium nucleatum and that this uptake process was also dependent on lipid components [ 14 ]. When lipids were removed, the uptake of tomato-derived nanovesicles by Fusobacterium nucleatum was reduced and their growth state was restored [ 14 ]. In turn, nanovesicles reconstituted by cholesteryl esters (CE) were able to be taken up by Fusobacterium nucleatum [ 14 ].…”
Section: Endocytosis: Specific Recognition and Uptake By Microbial Co...mentioning
confidence: 99%
See 3 more Smart Citations